Analisis Profitabilitas dan Risiko Operasional Restoran Ayam Bakar Menggunakan Simulasi Monte Carlo - Silmy, Muhammad Ashbar As; Nasution, Muhammad Rizky Akbar; Adriansyah, Ryan; Atilasyah, Radith; Setiawan, Ryu Arfan (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the profitability and operational risk of a grilled chicken restaurant using a Monte Carlo simulation approach based on historical data from 2022–2026. The analyzed variables include number of customers, selling price, raw material cost, and fixed operational cost. A mathematical profit model was simulated through 10,000 iterations to obtain the probability distribution of daily profit. The results indicate an expected daily profit of approximately IDR 1.57 million with a very high probability of positive returns and minimal risk of loss. Correlation analysis reveals that price has a positive relationship with profit; however, the number of customers is identified as the most dominant factor influencing profitability. The stable convergence of the simulation confirms the reliability and validity of the model. These findings demonstrate that Monte Carlo simulation is an effective decision-support tool for financial feasibility evaluation and risk management in the culinary business sector.